Fast and low-complexity video down-sizing transcoder - Zhuo-yi LV; Ke-bin JIA; Wan-chi WIU (Tongxin xuebao)
An efficient mode decision scheme for down-sizing video transcoding in H.264 using support vector machines (SVM)was proposed.In order to reduce the high computationa complexity of using conventional mode decision in the H.264 re-encoder,the proposed scheme used SVM to exploit the correlation between coding information extracted from the input high-resolution bit-stream and the coding modes of macro-blocks in down-sized video frames.The key techniques of training and predicting SVM including feature vector and kernel function were studied and then the SVM model was trained.After the hierarchical SVM classifier,improbable modes were eliminated and only a small number of candidate modes were carried out using the RDO operations.Hence,remarkable computing time could be saved,up to 67.31%,while maintaining nearly the same quality of the transcoded pictures.